Ansietas Menghadapi Ujian Nasional pada Siswa SMP dan SMA - Irra Wiryani; Ice Yulia Wardani (Jurnal Keperawatan Indonesia, 2016)
Ujian nasional (UN) yang diadakan pemerintah setiap tahun menimbulkan masalah ansietas bagi para siswa SMP dan SMA. Penelitian ini bertujuan mengidentifikasi gambaran tingkat ansietas siswa menghadapi ujian nasional pada siswa SMP dan SMA. Desain penelitian deskriptif dengan melibatkan 83 siswa SMPN dan 80 siswa SMAN yang akan menghadapi UN. Instrumen yang digunakan adalah modifikasi wetside test anxiety scale. Hasil penelitian didapatkan 11% siswa SMPN ansietas tingkat sedang sampai dengan berat dan 39,2% siswa SMAN ansietas pada tingkat sedang sampai dengan berat. Perawat sekolah perlu melakukan intervensi untuk mengurangi ansietas siswa di sekolah terutama menjelang UN. Diharapkan pihak sekolah dan orang tua dapat meningkatkan perhatiannya terhadap masalah psikologis siswa. Abstract The Anxiety of Junior High School and Senior High School Students Toward National Exam. National Exam held by government evoked anxiety problem among students. Junior and Senior High School students are the majority participant who shows anxiety problem. This research is aimed to identify the description of student’s level anxiety who will encounter the National Exam in SMPN and SMAN at Depok. This study used description survey involving 83 Junior School students and 80 Senior School students. To measure the level of anxiety among students was used Wetside test anxiety scale. The result shows 11% of Junior School students identified anxiety in moderate to severe scale, and 39.2% Senior School students shows anxiety level from moderate to panic scale. This result indicates despite the majority result of student’s level of anxiety in mild scale, nursing intervention is required to reduce the level of anxiety among students, especially for students who will encounter National Exam and being identified in the level of anxiety at moderate to panic scale. The teachers and parents is expected to provide more attention to student’s psychological problems. Key words: anxiety, national final exam, students